ANALISA PENGARUH SUHU PERLAKUAN PANAS TERHADAP PROPERTI MEKANIK KOMPOSIT AL-TIC 3% DENGAN METODE COOLING SLOPE SUDUT KEMIRINGAN 45° - Farida Ariani; Diky Setiawan Hutabarat (Jurnal Rekayasa Mesin, 2023)
On the industrial side, the selection of materials for a product produced by a company must be following the function and purpose of the product. There are many types of materials used by various companies in the manufacture of a product, one of which is aluminium. This study aims to determine the effect of temperature variations of 3% Al-TiC Composite Heat Treatment 350°C, 450°C, 550°C on the mechanical properties and microstructure with the cooling slope method. The casting process is carried out using A356 aluminium material and the addition of 3% titanium carbide (TiC). The casting results are poured into a permanent mould through a cooling slope with a pouring angle of 45°. And finally carried out by heat treatment on the test object with temperature variations of 350°C, 450°C, 550°C with oil cooling media SAE 40. The highest hardness was obtained at a heat treatment temperature of 550°C with a value of 64.25 BHN, at a temperature of 450°C with a value of 60.02 BHN, and 350°C with a value of 56.59 BHN. The highest tensile strength was obtained at a heat treatment temperature of 550°C of 219,862 MPa, a temperature of 450°C of 183,273 MPa, and 350°C of 164,328 MPa. The obtained microstructure shows hypo-eutectic silicon dispersed among the aluminium. The microstructure shows that the homogenization of silicon and TiC at a heat treatment temperature of 550°C is very good, as evidenced by the uniformly dispersed density of the alloy filling the aluminium matrix.